91.9k views
1 vote
Please help ASAP.. Question below

Please help ASAP.. Question below-example-1
User Geroge
by
5.2k points

2 Answers

4 votes

Answer:

option B and option D

0 and 2

Explanation:

Given in the question two functions

f(x) = x² - 4x + 3

g(x) = -x² + 3

f(x) = g(x)

x² - 4x + 3 = - x² + 3

Rearrange the like terms, x terms to the left and constant term to the right.

x²+ x² - 4x = 3 - 3

2x² - 4x = 0

Divide by two

2x²/2 - 4x/2 = 0/2

x² - 2x = 0

Take x as a common term

x(x-2) = 0

so

x = 0

or

(x-2) = 0

x = 2

User Saneshark
by
5.3k points
3 votes

Answer:

0

3

Explanation:

The given functions are


f(x)=x^2-4x+3

We can rewrite this function in the vertex form to obtain;


f(x)=(x-2)^2-1

This is the graph of the parent function
h(x)=x^2 shifted, 2 units to the right and 1 unit down.

The second function is


g(x)=-x^2+3

This is the graph of the parent function
h(x)=x^2 reflected in the x-axis and shifted up 3 units.

The graph of the two functions are shown in the attachment.

The solution to f(x)=g(x) is where the two graphs meet.

The two graphs intersected at

(0,3) and (2,-1)

Please help ASAP.. Question below-example-1
User Krystian
by
5.4k points